NYANYIAN RAKYAT SENTANI DAN DINAMIKA BAHASA INDONESIA - Modouw, Wigati Yektiningtyas (ATAVISME, 2008)
Papua is famous for folklore. One of Papuan folklores is ehabla, an oral poem from Sentani, Jayapura. Interestingly, ehabla does not only represent culture and local wisdom of Sentani community, but also contributes to the enrichment of Indonesian vocabulary. The lexicons used to express the idea in the ehabla, especially ones that cannot be homologically translated into bahasa Indonesia, can be used as lexical alternatives.